2005
DOI: 10.1111/j.1365-2796.2005.01507.x
|View full text |Cite
|
Sign up to set email alerts
|

Low level of tissue plasminogen activator activity in non‐diabetic patients with a first myocardial infarction

Abstract: Abstract. Lundblad D, Dinesen B, Rautio A, Røder ME, Eliasson M (Sunderby Hospital, Luleå; University of Umeå, Umeå, Sweden; Steno Diabetes Center, Gentofte; and University of Copenhagen, Copenhagen NV, Denmark). Low level of tissue plasminogen activator activity in non-diabetic patients with a first myocardial infarction. J Intern Med 2005; 258: 13-20.Objective. To explore the role of tissue plasminogen activator (tPA) activity and plasminogen activator inhibitor type 1 (PAI-1) in survivors of a first myocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…A problem concerning the measurement of both tPA and PAI-1 levels is that the levels have a strong diurnal variation, which could influence the results if measurements are not performed following standardized procedures. 60 Most population-based studies found increased PAI-1 antigen or activity levels to be associated with increased risk of arterial disease in unadjusted models or models only adjusted for age and sex, 37,38,[61][62][63][64][65][66][67][68] as did cohort studies including patients with angina or other preexisting arterial disease. 21,22,69 No association between PAI-1 and arterial events during follow-up was found in two prospective studies on patients with coronary heart disease 70 or severe angina pectoris.…”
Section: Nonfibrinolytic Properties Of Plasminmentioning
confidence: 99%
See 1 more Smart Citation
“…A problem concerning the measurement of both tPA and PAI-1 levels is that the levels have a strong diurnal variation, which could influence the results if measurements are not performed following standardized procedures. 60 Most population-based studies found increased PAI-1 antigen or activity levels to be associated with increased risk of arterial disease in unadjusted models or models only adjusted for age and sex, 37,38,[61][62][63][64][65][66][67][68] as did cohort studies including patients with angina or other preexisting arterial disease. 21,22,69 No association between PAI-1 and arterial events during follow-up was found in two prospective studies on patients with coronary heart disease 70 or severe angina pectoris.…”
Section: Nonfibrinolytic Properties Of Plasminmentioning
confidence: 99%
“…77 However, two cohort studies and two casecontrol studies have found elevated tPA activity to decrease the risk of arterial disease. 64,66,69,70 In the PLAT study, tPA release after venous stasis at baseline was increased in patients with a major atherothrombotic event, compared with those who remained free of events after 2 years of follow-up. 22 However, in another cohort study on patients with coronary heart disease, patients with a decreased tPA release after venous occlusion had a higher risk of myocardial infarction, ischemic stroke, or unstable angina during follow-up of 42 months.…”
Section: Tpa Activity and Tpa Release After Stimulationmentioning
confidence: 99%
“…Increased plasminogen activator inhibitor‐1 (PAI‐1) activity or antigen has been found to be associated with an increased risk of first and recurrent arterial diseases (Takazoe et al , 2001; Smith et al , 2005). However, other studies found no association (Wiman et al , 2000; Mannucci et al , 2005) or the risk associated with increased PAI‐1 levels disappeared after adjustment for markers of insulin resistance (Ladenvall et al , 2002; Lundblad et al , 2005). Several studies have shown a positive association between tissue‐type plasminogen activator (t‐PA) and the risk of myocardial infarction (Thogersen et al , 1998; Zorio et al , 2003; Mannucci et al , 2005), although this could not be confirmed in the Caerphilly study, a large prospective study (Smith et al , 2005).…”
mentioning
confidence: 97%
“…Verschiedene Studien konnten keine Assoziation zwischen PAI-1-Spiegeln und Myokardinfarkt oder ischämischem Hirninfarkt zeigen (10,31,42,62). In anderen Studien war eine Beziehung zwischen erhöhter PAI-1-Konzentration und arteriellen Gefäßverschlüssen nachweisbar, die allerdings in der multivariaten Analyse unter Hinzunahme von Faktoren der Insulinresistenz ihren prädiktiven Wert verloren (2,34,40,46,57,64).…”
Section: Pai-1unclassified